Improved synthesis of reduced graphene oxide-titanium dioxide composite with highly exposed {001} facets and its photoelectrochemical response - Thien, Gregory Soon How; Omar, Fatin Saiha; Ahmad Blya, Nur Ily Syuhada; Chiu, Wee Siong; Lim, Hong Ngee; Yousefi, Ramin; Sheini, Farid Jamali; Huang, Nay Ming (Hindawi Publishing Corporation, 2014)
Crystal facet engineering has attracted worldwide attention, particularly in facet manipulation of titanium dioxide (TiO2) surface properties. An improved synthesis by solvothermal route has been employed for the formation of TiO2 with highly exposed {001} facets decorated on reduced graphene oxide (RGO) sheets. The RGO-TiO2 composite could be produced with high yield by following a stringently methodical yet simple approach. Field emission scanning electron microscope and high resolution transmission electron microscope imaging reveal that the structure consists of TiO2 nanoparticles covered with TiO2 nanosheets of exposed {001} facets on a RGO sheet. The photocurrent response of the RGO-TiO2 composite was discovered to outperform that of pure TiO2, as a 10-fold increase in photocurrent density was observed for the RGO-TiO2 electrodes. This may be attributed to rapid electron transport and the delayed recombination of electron-hole pairs due to improved ionic interaction between titanium and carbon.